1998
DOI: 10.1097/00006534-199812000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Longitudinal Changes in Rheumatologic Parameters after Silicone Breast Implantation: A Prospective 13-Year Study

Abstract: There have been numerous questions regarding the association of polysiloxane with connective tissue disease and alteration of host immune response. C-reactive protein, rheumatoid factor, and anti-streptolysin-O titers were measured in 218 patients. These studies are routinely used in the diagnosis of autoimmune disease and mixed connective tissue disease. This prospective study has been in progress since 1985. The first patients were seen in July of 1985, and those individuals willing to participate were follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The most convincing of these investigations involved approximately 6 [17][18][19][20][21][22] large retrospective cohort studies that followed up patients with breast implants for up to 10 years or longer and detected no increased associated risk of connective tissue disease, such as rheumatoid arthritis, scleroderma, systemic lupus erythematosus, polymyositis/dermatomyositis, Sjögren syndrome, and mixed connective tissue disease. At least 3 of these studies, from the Mayo Clinic (Rochester, Minn), Sweden, and Denmark, aspired to being population based; in the United States, several large studies based on querying female health professionals enrolled up to several hundred thousand subjects each, thus greatly minimizing the risk that even small adverse effects would fail to be detected owing to inadequate sample size.…”
Section: Major Epidemiologic Investigations Of the Association Betweementioning
confidence: 99%
“…The most convincing of these investigations involved approximately 6 [17][18][19][20][21][22] large retrospective cohort studies that followed up patients with breast implants for up to 10 years or longer and detected no increased associated risk of connective tissue disease, such as rheumatoid arthritis, scleroderma, systemic lupus erythematosus, polymyositis/dermatomyositis, Sjögren syndrome, and mixed connective tissue disease. At least 3 of these studies, from the Mayo Clinic (Rochester, Minn), Sweden, and Denmark, aspired to being population based; in the United States, several large studies based on querying female health professionals enrolled up to several hundred thousand subjects each, thus greatly minimizing the risk that even small adverse effects would fail to be detected owing to inadequate sample size.…”
Section: Major Epidemiologic Investigations Of the Association Betweementioning
confidence: 99%
“…Based on some early case reports about possibly toxic rheumatologic effects of silicone breast implants, large‐scale litigation ensued which cost the manufacturer billions of dollars, created immense worry in patients who had these implants, and generated huge amounts of money for attorneys. Subsequent cohort and case‐control studies have shown no evidence for a link between breast implants and rheumatologic disease 28–32 …”
Section: Concepts In Critical Appraisalmentioning
confidence: 99%